An experimental and simulation study of binary adsorption in metal-organic frameworks - Yang, Y.; Sitprasert, C.; Rufford, T.; Ge, L.; Shukla, P.; Wang, Shaobin; Rudolph, V.; Zhu, Z. (Elsevier, 2015)
Large surface area, high gas adsorption capacity and convenient synthesis methods make microporous metal–organic frameworks (MOFs) a promising adsorbent for gas separation of CO2/N2 and CO2/CH4. This study examines the selective adsorption of CO2 on MOFs through the experimental measurement of equilibrium adsorption capacities from pure fluids (CO2, CH4 and N2) and mixtures of CO2/N2 and CO2/CH4. The derived adsorption selectivity from binary adsorption measurements is higher than the ideal selectivity. Comparing with direct binary adsorption experiments, the Ideal Adsorbed Solution Theory (IAST) model using best-fit parameters for Langmuir isotherms of each pure fluid provides satisfactory predictions for the binary mixtures of CO2/N2 and CO2/CH4. This combined experimental and modeling approach can provide criteria to screen metal–organic frameworks for the separation of gas mixtures at industrially relevant compositions, temperatures and pressures.